1899 Annotated Statutes of the Indian Territory, at 757, ch. 136, § 4345 - (:unkn) unknown (My University, 1899)
Every person other than an Indian, who within the Indian country, purchases or receives of any Indian in the way of barter, trade or pledge, a gun, trap or other article commonly used in hunting, any instrument of husbandry, or cooking utensils of the kind commonly obtained by the Indians in the intercourse with the white people, or any article of clothing except skins or furs, shall be liable to penalty of fifty dollars.
Keywords: TRANSFER - DANGEROUS PERSONS